ANALISIS PEMANFAATAN PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR - Melsika Melsika; Fauzana Annova (CV. ADIBA ASIHA AMIRA, 2024)
This research aims to determine the use of school libraries as learning resources. In writing this article, the author used a type of literature or library research. This research collects in-depth information and data through literature, books, magazines, appropriate previous research results, as well as other references in order to obtain answers and theoretical foundations regarding the problems studied. The data collection technique applied in this research is by collecting data from scientific works in the form of books, journals, magazines, theses and various other scientific papers both online and offline. The library data obtained is then collected and processed through editing, organizing and finding processes. The research results show that: 1) the use of the library as a learning resource seen from the intensity of visits is 2-3 times a week. The types of activities carried out include assignment activities from teachers, collection utilization activities, and facility utilization activities. 2) Factors that influence the level of library utilization are library comfort, completeness of collections, availability of facilities, library services, and also the interests and needs of visitors. 3) The advantages of libraries are that the space design is not monotonous, complete collections, complete facilities and infrastructure, and good service. Meanwhile, the weaknesses are the slow renewal of competition supporting collections, the slow repair of problematic facilities.